nApoli: uma ferramenta web para análise de interações proteína-ligante - Alexandre Victor Fassio (2015)
Elucidating the mechanisms involved in the molecular recognition and which forces contribute to the recognition is a central problem in biology, since the interactions between two molecules are extremely important to biological systems as a whole and are very toilsome to be predicted even for small molecules. Therefore, we propose an easy and intuitive tool through visual strategies to depict the patterns and the types of interactions established between proteins and their ligands. In order to achieve it, we propose nAPOLI (Analysis of PrOtein Ligand Interactions), an interactive web tool to study the protein-ligand interactions in large scale by using visual strategies and statistical analysis. We performed a case study consisting of 73 inhibitors to the human protein CDK2 (Ciclin-dependent kinase 2). nAPOLI showed to be very useful as itshed some light on the problem of discovering what is conserved in a set of ligands and which interactions they establish with a receptor. Through this tool, we were able to confirm literature experimental results. Despite of the existance of other tools to analyse protein-ligand interactions, none of them present statistical, visual and interactive analysis in large scale. The tool can be accessed in: http://www.napoli.dcc.ufmg.br/